2009
DOI: 10.1071/ah090671
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of community-based resources for management of diabetes-related foot disorders in an Australian population

Abstract: We aimed to evaluate service model configuration, service capacity and accessibility of diabetes-related footcare in an Australian community health setting. Eighty-eight community-based podiatry clinics were surveyed using the selfadministered Footcare Provider Survey. Survey domains included communication, resources, service coordination and barriers to service provision. Sixty-nine from a possible 88 Victorian community podiatry clinics (78%) responded. Sixtyone (88%) provided ongoing care to individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The use of the risk classification system ensures the model has a sound evidence base, and the use of the available health service resources are driven by the clinical needs of the patients matched with the appropriate skill‐set of the service providers. The podiatric care of people with diabetes in Australia requires the development of a seamless and collaborative model of care established within and across different health settings, with a clear definition of what role each health service has with respect to the obligations to the patient group [7, 45].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the risk classification system ensures the model has a sound evidence base, and the use of the available health service resources are driven by the clinical needs of the patients matched with the appropriate skill‐set of the service providers. The podiatric care of people with diabetes in Australia requires the development of a seamless and collaborative model of care established within and across different health settings, with a clear definition of what role each health service has with respect to the obligations to the patient group [7, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Other Australian studies reporting higher use of the diabetic foot guidelines sampled podiatrists only, rather than the multidisciplinary sample in this study [ 57 , 58 ]. Improvement in healthcare practitioners’ diabetic foot knowledge in multidisciplinary samples has been shown in other studies using a pre/post-test design and continuing medical education [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the recommendations outlined in Australian National Evidence-Based Guideline on the Prevention, Identification and Management of Foot Complications in Diabetes apply directly to care provided by podiatrists [ 4 ]. However, there is limited literature examining how podiatrists’ clinical practice reflects evidence based practice in Australia [ 10 , 16 ]. One study surveying podiatry centres in Victoria reported over 60% of centres broadly used clinical guidelines when managing patients with diabetic foot disorders but did not provide further detail about compliance with specific guideline recommendations [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited literature examining how podiatrists’ clinical practice reflects evidence based practice in Australia [ 10 , 16 ]. One study surveying podiatry centres in Victoria reported over 60% of centres broadly used clinical guidelines when managing patients with diabetic foot disorders but did not provide further detail about compliance with specific guideline recommendations [ 16 ]. It has also been identified that the Australian Government’s Medical Benefits Schedule (MBS) does not attribute funding to many of the key evidence based recommendations outlined in the Australian guidelines, such as total contact casting or other devices rendered irremovable [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation